Pepper Waste as a Substitute To Conventional Fossil Fuel - John Melvin, Peter (Universiti Malaysia Sarawak, (UNIMAS), 2009)
Energy is an important essence of human's daily lives on earth. However, it was found that we had been using energy excessively, especially fossil fuels that had contributed to various problems on earth such as global warming phenomenon. Pepper waste has a great potential to be transformed into renewable resource because Malaysia is the fifth largest pepper producer in the world. This research paper investigates whether converting pepper waste into renewable energy such as ethanol and Biodiesel is feasible or not. The research paper had concluded that co-firing is the best way to utilize pepper waste as a renewable resource at the present time after thorough studies of other technologies such as boiler, gasification and anaerobic. These technologies are compared in terms of cost, fesibility, compatibility and efficiency. Besides that, the market model and potential problems that will be faced during the implementation of pepper waste as a renewable resource are also determined